Georg Jensen : A tradition of splendid silver - Drucker, Janet (Atglen : Schiffer, 1997)
Georg Jensen (1866 - 1935) is zilversmid en ontwerper.
With update price guide
Engels
boek
Keywords: Jensen, Georg; 19de eeuw; Denemarken